Targeting Conservation Policy - Smale, Melinda; King, Amanda (International Food Policy Research Institute, 2005)
Analysis of the determinants of on-farm crop diversity not only enables researchers to predict the distribution of diversity across landscapes, but also to develop programs or recommend policies that might positively affect its conservation. This can be accomplished in two ways: either directly, or through policies that influence factors linked with higher levels of crop diversity.